FRI0293 EFFECTIVENESS OF SWITCHING BETWEEN TNF INHIBITORS IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS: IS THE REASON TO SWITCH RELEVANT?. (2nd June 2020) - Rodrigues-Manica, S.; Sepriano, A.; Pimentel Dos Santos, F.; Gouveia, N.; Barcelos, A.; Branco, J.; Bernardes, M.; Ferreira, R.; Vieira-Sousa, E.; Barreira, S. C.; Vinagre, F.; Roque, R.; et al.
Abstract : Background: It has been common practice to start a second TNF inhibitor (TNFi) in patients with axial spondyloarthritis (axSpA) who discontinue their first TNFi. It remains unclear if the reason for discontinuation of the first TNFi influences the response to the second. Objectives: To assess if the reason of discontinuation of the first TNFi influences the response to the second TNFi. Methods: Patients with axSpA from the ReumaPt registry, who discontinued their first TNFi and started a second TNFi and who had complete data on Ankylosing Spondylitis Disease Activity Score (ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) at baseline, 3 and 6 months for their first TNFi were included. Then, they were followed every 6 months up to 12 years. The main outcome was the ASDAS clinically important improvement (ASDAS CII). Secondary outcomes were ASDAS major important improvement (ASDAS MI); ASDAS low disease activity (ASDAS LDA); ASDAS inactive disease (ASDAS ID) and BASDAI 50. The reason for discontinuation of the first TNFi was defined as: i) Primary failure, ASDAS CII was not achieved at 3 or 6 months; ii) Secondary failure, ASDAS CII achieved at 3 or 6 months but lost in ≥1 follow-up visit; iii) Adverse events; iv) Other (e.g. pregnancy, surgery). The response to the first TNFi at 3 and 6 months was compared to the response to the second TNFi at the same visits, adjusting for age, gender and C-reactive protein (CRP). The association between the reason of discontinuation of the first TNFi and response the second TNFi over time was tested in generalized estimating equations (GEE) models, adjusted for age, gender and CRP. Results: In total, 193 patients (53% male, mean age 45 (SD:11) years) were included, with a median follow-up time on the second TNFi of 1.5 years. Patients had a lower response to the second TNFi compared to the first TNFi according to the main outcome (ASDAS CII) at 3 months (41% vs 51%) and 6 months (35% vs 56%). There was an association between the reason to discontinue the first TNFi and response to the second TNFi as defined by the most stringent outcomes (ASDAS MI and ASDAS ID), but not for ASDAS CII (Table). Compared to patients who discontinued their first TNFi due to primary failure, patients were more likely to achieve ASDAS ID with the second TNFi when they discontinued their first TNFi due to secondary failure (OR: 7.3 [(95%CI: 1.9; 27.7]), adverse events (OR: 9.1 [2.5; 33.3]), or other reasons (OR: 7.7 [1.6; 37.9]). Conclusion: In axSpA, response to the second TNFi is worse compared to the first TNFi. Patients with a secondary failure to the first TNFi have a better response to the second TNFi compared to those discontinuing the first TNFi due to primary failure, particularly for most stringent outcomes. Disclosure of Interests: Santiago Rodrigues-Manica Speakers bureau: Jansse, MSD, Novartis, Alexandre Sepriano: None declared, Fernando Pimentel dos Santos Speakers bureau: Novartis, Pfizer, Biogen, Vitoria, , Nélia Gouveia: None declared, Anabela Barcelos Speakers bureau: Bene, Eli-Lilly, Pfizer, MSD, Novartis, Jaime Branco Speakers bureau: Vitoria, Miguel Bernardes Speakers bureau: Abbvie, Amgen, Biogen, Eli-Lilly, Glaxo-Smith-Kline, Pfizer, Janssen, Novartis, Raquel Ferreira: None declared, Elsa Vieira-Sousa: None declared, Sofia C Barreira: None declared, Filipe Vinagre: None declared, Raquel Roque: None declared, Helena Santos Speakers bureau: AbbVie, Eli-Lilly, Janssen, Pfizer, Novartis, Nathalie Madeira: None declared, João Rovisco: None declared, Alexandra Daniel: None declared, Sofia Ramiro Grant/research support from: MSD, Consultant of: Abbvie, Lilly, Novartis, Sanofi Genzyme, Speakers bureau: Lilly, MSD, Novartis